Penerapan English Song dalam Mengenalkan Bahasa Inggris di Taman Kanak-kanak Yari Internasional School - Angelina Sitorus , Hanna; Suryana, Dadan (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
Songs are an excellent way to teach English to young children so that they can actually support their capacity to recite and recall basic English vocabulary and expressions, which is the basis of this post. This study also attempts to determine the viability and usefulness of using the English song to teach English to kindergarten students at Yari International School. The ability of children to understand concepts of speaking, reading, and writing is one of the English recognition skills that will be tested. This study employs a descriptive qualitative methodology. Additionally, this study employs methods for gathering data such as observation, interviews, and documentation. The author's method of data analysis includes data reduction, data presentation, and conclusion